Guide to IBM PC communications - Kruglinski, David (Berkeley, Calif. : Osborne/McGraw-Hill, 1984)
The book explains the essentials of using IBM PC to access the vast store information available through high -speed computer networks
Includes index.
Bibliography: p. 275-277.
ii 15/01/2019
Loans
Keywords: Data transmission systems; IBM Personal Computer